KECERDASAN VERBAL DALAM PERSPEKTIF AL-QUR’AN - Nur Arfiyah Febriani; Sri Tuti Rahmawati (Lembaga Penelitian dan Studi kebijakan MADANI Instutute, 2021)
The conclusions of this dissertation are: Verbal intelligence from the perspective of the Koran carries a transcendental transformative informative theory. This is based on the qaul (verbal) expression which is informative which means ensuring the meaning of the message reaches the communicant, with several types of expressions, such as: 1. Qaul Maisûr/phrases that are easy to understand, 2. Qaul Baligh/phrases whose message is conveyed, and; 3. Qaul Ma'ruf /expressions with attention to local culture. As for Qaul which is transformative, which means speech that is able to change the communicant to the understanding and application of Islamic teachings which is better used by the Koran with the words: 1. Qaul Sadîd /words/words that are on target, 2. Qaul Ahsan/speech or the best words, 3. Qaul Tsâbit/strong and lasting speech, 4. Qaul Layyin/uangkap who is gentle, 5. Qaul Thayyib/good expressions or speech (diction is not dirty), and; 6. Qaul Salâm/expressions or sayings that are full of peace. Qaul that is transcendental is Qaul al-Haqq/haqq speech (based on Islamic texts), namely: 1. Qaul Fashl /words from wise thoughts to reveal what is haqq and what is falsehood, 2. Qaul Tsâqil /yang means heavy utterances that are full of divine values, 3. Qaul Râdhiyan/sayings or expressions that are blessed by Allah, 4. Qaul 'Adzim words or expressions of great value with Allah, and 5. Qaul Karîm: sayings or words that are noble. This dissertation also reveals that the purpose of transformation in verbal communication can be realized if there is an interrelation between communicators (Surat ar-Rahman/55: 4), methods (Surat an-Nahl/16: 125), material (Surat al-Isra '/17: 36) and the communicants (Surat an-Nisa '/4: 164).The theory of verbal intelligence from the perspective of the Koran is an interrelation theory that combines the informative theory introduced by Claude Shannon (1948) and the transformative theory introduced by (Jack Mezirow (1978),